2018
DOI: 10.1088/1361-6587/aaa556
|View full text |Cite
|
Sign up to set email alerts
|

Ion acceleration in electrostatic collisionless shock: on the optimal density profile for quasi-monoenergetic beams

Abstract: A numerical study on ion acceleration in electrostatic shock waves is presented, with the aim of determining the best plasma configuration to achieve quasimonoenergetic ion beams in laser-driven systems. It was recently shown that tailored near-critical density plasmas characterized by a long-scale decreasing rear density profile lead to beams with low energy spread [F. Fiúza et al., Physical Review Letters 109, 215001 (2012)]. In this work, a detailed parameter scan investigating different plasma scale lengt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…For simplicity, the near-critical plasma is assumed to be composed of only hydrogen ions H + and electrons both with the initial temperature of 1 keV. The plasma electron density has a tailored profile with a rapid 10 μm linear rise starting at x=−10 μm to the peak density 12n c at x=0 and then followed by an exponentially falling with 5 μm scale length, which satisfies the optimized density profile of CSA [27,28,35]. The high-Z solid tube is assumed to have a high electron density of 50n c , tube length of 300 μm and wall thickness of 1 μm.…”
Section: Target Design and Pic Simulation Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…For simplicity, the near-critical plasma is assumed to be composed of only hydrogen ions H + and electrons both with the initial temperature of 1 keV. The plasma electron density has a tailored profile with a rapid 10 μm linear rise starting at x=−10 μm to the peak density 12n c at x=0 and then followed by an exponentially falling with 5 μm scale length, which satisfies the optimized density profile of CSA [27,28,35]. The high-Z solid tube is assumed to have a high electron density of 50n c , tube length of 300 μm and wall thickness of 1 μm.…”
Section: Target Design and Pic Simulation Setupmentioning
confidence: 99%
“…So a strong collisionless shock with the Mach number > M 1.6 and the large shock velocity v sh >v hb is formed. Based on this model, the required laser and target matching condition for production of high-quality ion beams by CSA has been given in [27,28,35], which, however, is under the assumption of the reduced one-dimensional geometry. The specific optimal tailored density profile required for launching the shock is proposed in order to both avoid strong TNSA field that broadens the energy spread and ensure uniform plasma heating [27,28,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently suggested that ignition could be achieved with ions generated via collisionless shocks excited directly in the plasma corona surrounding the compressed pellet [10][11][12][13][14][15][16][17]. Indeed laser-driven shock waves provide an efficient mechanism to accelerate highquality ions with average energies of some MeVs [18][19][20][21][22][23][24][25][26]. Furthermore, compared to TNSA the scheme seems advantageous, not only because of the lower energy spread and divergence of the ions [25], but also because exciting the shock in the corona plasma would eliminate the need for an external target, thus reducing the distance between the ion source and the core.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in laser technology (intensities in excess of 10 19 W/cm 2 with laser pulse durations shorter than 1 ps and high-resolution diagnostics) open the possibility to probe such processes through laser-solid interactions [19,[21][22][23][24]. In these experiments, the magnetic field generation is often attributed to the Biermann battery [20,25,26].…”
mentioning
confidence: 99%